PB16. Prefrontal bipolar versus multichannel tDCS: Impact on working memory performance. Issue 8 (August 2018) - Splittgerber, M.; Maack, M.; Brauer, H.; Breitling, C.; Prehn-Kristensen, A.; Krauel, K.; Miranda, P.; Nowak, R.; Siniatchkin, M.; Moliadze, V.
Abstract : Introduction: Recent studies show that tDCS applied over the left dorsolateral prefrontal cortex (lDLPFC) can successfully affect working memory (WM) performance (Coffman et al., 2014 ). The present study investigates the influences of a classical bipolar and more focal multichannel tDCS over the lDLPFC on WM performance (2-back task) and continuous performance task (CPT) as non target task as well as on resting-state EEG oscillations and ERPs. Methods: The study was approved by the Ethic Committee of the Faculty of Medicine Christian-Albrechts University Kiel. Eighteen healthy young adults (18–30 years) participated in the study. Participants were stimulated 3 times (bipolar, multichannel, sham stimulation in randomized order) over the lDLPFC for 20 min, minimum period between sessions was 7 days. For bipolar stimulation 1 mA was applied by two circular saline-soaked surface sponge electrodes (25 cm 2 ), with anode positioned over F3 and reference over FP2. For multichannel tDCS we used five 3.14 cm 2 circular PiStim electrodes (Neuroelectrics, Barcelona, Spain), positioned at AF3 (897 uA), AF7 (284 uA), F3 (819 uA), FP2 (−1000 uA) and T7 (−1000 uA). After stimulation EEG at rest (2 min eyes closed, 2 min eyes open) and during 2-back and CPT performance was recorded. Results: Behavioral results show significant improvement of accuracy in the 2-back task after multichannel and bipolar tDCS compared to sham stimulation but not for CPT performance. Incidence and intensity of aversive side effects did not differ between multichannel, bipolar or sham tDCS. Conclusion: Our results show that multichannel and bipolar tDCS over the lDLPFC have the potential of modulating WM performance, with multifocal stimulation not eliciting greater effects, which is in contrary to results of motor cortex area stimulation (Fischer et al., 2017 ). Since WM performance but not non target-task performance was affected, our results suggest that the area of interest has been successfully stimulated. Our results on aversive side effect underline the tolerability of multichannel tDCS and bipolar tDCS. Additionally, participants were not able to discriminate real and sham stimulation effectively. However, future analyses, especially of obtained EEG data, will give further insight on the efficacy and tolerability of multichannel tDCS versus bipolar tDCS. This study was conducted as part of the STIPED program. STIPED has received funding fromEuropean Union's Horizon2020 research and innovation programme under grant agreement No.731827 .